Cognition-Based Strategy Model: A Cognitive Approach to Organizational Strategy Formulation and Implementation - Feinnudin, Agung; Wahono, Puji (SAFE-Network, 2025)
This study explores how cognitive factors influence strategy formulation and implementation within a public sector organization. Using a qualitative approach, comprising in-depth interviews, exploratory questionnaires, and documentation analysis, it was found that strategic decisions are not solely based on rational, data-driven analysis but are deeply shaped by cognitive frames, mental maps, and the subjective interpretations of leaders. Variations in strategic intent, perception of risks and opportunities, and resistance to change often stem from individual cognition rather than structural constraints. These findings highlight the important role of mental models and strategic intuition in shaping policy direction and suggest that aligning cognitive understandings across units is essential for coherent strategy execution. The study offers both theoretical insights and practical recommendations for improving strategic alignment through cognitive tools and organizational learning.